Sharp Estimates for the Best Approximations of Smooth Functions in C 2π in Terms of Linear Combinations of the Modules of Continuity of Their Derivatives - Babich, Yurii P.; Mykhailova, Tetiana F. (Ukrainian Mathematical Journal, Kyiv, 2022)
ENG: For the best approximations of en-1(ƒ) functions from C12π by trigonometric polynomials, Zhuk earlier proved the exact Jackson inequality en-1(ƒ),,π/4n*ɷ(ƒ',π/n). This paper proves the following version of Jackson's exact inequality: en-1(ƒ),,π/4n*﴾(1/2ɷ(ƒ',π/2n)+1/2ɷ(ƒ',π/n)﴿.

UKR: Для найкращих наближень en-1(ƒ) функцій із C12π тригонометричними поліномами раніше Жук довів точну нерівність Джексона en-1(ƒ),,π/4n*ɷ(ƒ',π/n) . У даній роботі доведений такий варіант точної нерівності Джексона: en-1(ƒ),,π/4n*﴾(1/2ɷ(ƒ',π/2n)+1/2ɷ(ƒ',π/n)﴿.
Точні оцінки найкращих наближень гладких функцій в в C2π у термінах лінійних комбінацій модулів неперервності їхніх похідних
Т. Mykhailova: ORCID 0000-0003-4609-7744; Yu.Babich: ORCID 0000-0001-6612-715X
Keywords: modules of continuity; glad function; middles as Steklov; модулі непреривності; гладкі функції; усередження за Стєкловим; КВМ